Evaluation of efficiency of coating mortars with recycled additives applying Data Envelopment Analysis (DEA) (Publicaciones en Ciencias y Tecnología, 2018)
Among other priorities, the civil construction industry requires optimize its resources to streamline their processes. In this paper, the Data Envelopment Analysis (DEA) is applied to know the relative efficiency of the compressive strength of twelve (12) mortar mixtures of coatings (friezes), which have been analyzed in four (4) studies previously published. The efficiency of coating mortars with addition of recycled material such as steel fiber, lime, sugarcane bagasse (CBCA) and low density recycled plastic (LDPE) is assessed, by making the relative comparison of its compression resistances to Use them as an alternative to replacing stone materials. The efficiency of the mixtures of cement and sand without additive or with lime is corroborated and the efficiency of the use of CBCA (2.71 kg) and steel fiber (0.5 and 1 kg) is verified in mixtures of mortars of coating. It proposes potential improvements that specify the reductions in kilograms and percentages for the components and their contribution in calculating efficiency.
Keywords: friezes; additives; DEA; coating mortars; efficiency